Researching The Relation Between The Communicative Approach And Types Of Syllabi To Language Teaching - Fatima Bendoukha (Al-Lisaniyyat, 2023)
To increase learners’ engagement as well as learning, various theories and approaches have been developed to contribute to effective learning. The majority of the scientific tools and methods focus on the significance of the delivered learning channels and the ways of ensuring language acquisition. The current paper is designed to give the learning/ teaching population an idea about the philosophy of using certain tools of instruction and thereby describe the communicative as well as learner-centred¬ approaches and their underlying roles in language teaching especially when they are used and viewed in a holistic approach. The second point is that language designers are not only obliged to determine the necessary syllabuses to meet the needs of the language learners but also how they could be selected and mixed to reach the learning objectives. Résumé: Pour accroître l’engagement et l’apprentissage des apprenants, diverses théories et approches ont été développées afin de contribuer à un apprentissage efficace. La majorité des outils et méthodes scientifiques se concentrent sur l’importance des canaux d’apprentissage fournis et les moyens d’assurer l’acquisition de la langue. Le présent document est conçu pour donner à la population apprenante / enseignante une idée de la philosophie de l’utilisation de certains outils d’enseignement et décrire ainsi les approches communicatives et centrées sur l’apprenant et leurs principaux rôles dans l’enseignement des langues en particulier, lorsqu’ils sont utilisés et considérés dans une approche holistique. Le deuxième point est que les concepteurs de langues ne sont pas seulement tenus de déterminer les programmes nécessaires pour répondre aux besoins des apprenants de langues, mais aussi comment ils pourraient être sélectionnés et mélangés pour atteindre les objectifs d’apprentissage.